Pendidikan Pesantren : Pola Pembentukan Karakter Da'i Santri di Era Digital (Studi Kasus Ponpes Dalwa) - Ibad, M. Nashoihul; Dewantara, Muhammad Iqbal; Anurogo, Dito (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2025)
The integration of digital technology in Islamic educational institutions is increasingly essential in equipping students to address contemporary challenges. This study examines Pondok Pesantren Darullughah Wadda’wah (Dalwa), which effectively utilizes digital platforms such as Dalwa TV to enhance education and training of da’i among its 7,450 students among 4 universities. Established in 1981, the pesantren merges traditional religious education by integrating innovative digital approaches to create a holistic learning environment. The method used in this research include interviews, observations, and document analysis. The findings reveal that Dalwa integrates religious teachings with practical skills in communication and media production, enabling students to actively participate in digital dakwah. Furthermore, the pesantren incorporates syariah-based economic empowerment initiatives, offering students entrepreneurial experience. Despite challenges such as technological skill gaps, Dalwa addresses them through targeted training and infrastructure development. This study highlights the pesantren’s ability to adapt with digital era, producing competent da’i capable of navigating the complexities of modern society. Dalwa’s success exemplifies how Islamic institutions can innovate to remain relevant in a rapidly evolving technological landscape, providing a benchmark for other pesantren.